Graphene growth from photo-polymerized bi-phenylthiol self-assembled monolayers - Zehra, Tashfeen; Syari’ati, Ali; Ivashenko, Oleksii; Bignardi, Luca; Van Dorp, Willem F.; De Hosson, Jeff T. M.; Rudolf, Petra (Frontiers in Nanotechnology, 2024)
We present an enhanced methodology for the synthesis of graphene, from photo-polymerized self-assembled monolayers (SAMs) of 1,1ʹ-biphenyl-4-thiol on both electropolished and oxidized copper substrates. The SAMs were subjected to a two-step process involving light-induced polymerization followed by annealing in a vacuum furnace to yield the two-dimensional solid. Comprehensive characterization using contact angle measurements, X-ray photoelectron spectroscopy, and Raman spectroscopy, as well as scanning electron and transmission electron microscopy, provided conclusive evidence of growth of single-layer graphene. Notably, our findings revealed superior quality graphene on oxidized copper substrates compared to their electropolished counterparts, highlighting the impact of substrate choice on the quality of the resultant material.